Understanding gender dimensions of agriculture and climate change in smallholder farming communities - Jost, Christine; Kyazze, Florence Birungi; Naab, Jesse B.; Neelormi, S; Kinyangi, James; Zougmoré, Robert B.; Aggarwal, Pramod K.; Bhatta, Gopal Datt; Chaudhury, M.; Tapio-Bistrom, M.L.; Nelson, S.; Kristjanson, Patricia M. (Informa UK Limited, 2016)
In Uganda, Ghana and Bangladesh, participatory tools were used for a socio-economic and gender analysis of three topics: climate-smart agriculture (CSA), climate analogue approaches, and climate and weather forecasting. Policy and programme-relevant results were obtained. Smallholders are changing agricultural practices due to observations of climatic and environmental change. Women appear to be less adaptive because of financial or resource constraints, because of male domination in receiving information and extension services and because available adaptation strategies tend to create higher labour loads for women. The climate analogue approach (identifying places resembling your future climate so as to identify potential adaptations) is a promising tool for increasing farmer-to-farmer learning, where a high degree of climatic variability means that analogue villages that have successfully adopted new CSA practices exist nearby. Institutional issues related to forecast production limit their credibility and salience, particularly in terms of women ’ability to access and understand them. The participatory tools used in this study provided some insights into women’ adaptive capacity in the villages studied, but not to the depth necessary to address women" specific vulnerabilities in CSA programmes. Further research is necessary to move the discourse related to gender and climate change beyond the conceptualization of women as a homogenously vulnerable group in CSA programmes.